The role of public banks in the COVID-19 crisis - Trillo del Pozo, David; Alonso Gallo, Nuria (Papeles de Europa, 2021)
Public banks have taken on an unusual role in the economic crisis derived from the global pandemic experienced since 2020, insofar as they have served as a transmission belt for European aid to companies. However, this role has not been equally distributed in Europe. In the countries with the greatest implantation of public or development banking, in terms of budget volume and action network, it has been possible to quickly transmit financing. In other countries such as Spain it has been delays derived from the use of commercial banks as credit grantors. The article analyzes the public banking models in Europe through five representative countries and the impact of their actions in the aforementioned crisis.
Keywords: public bank; Economic crisis; COVID-19; Pandemic